2020
DOI: 10.1002/mds.28056
|View full text |Cite
|
Sign up to set email alerts
|

CSF NFL in a Longitudinally Assessed PD Cohort: Age Effects and Cognitive Trajectories

Abstract: BackgroundNeurofilament light protein is an unspecific biofluid marker that reflects the extent of neuronal/axonal damage and thereby offers the chance monitor disease severity and progression. The objective of this study was to investigate cerebrospinal fluid (CSF) levels of neurofilament light protein in Parkinson’s disease (PD) patients with clinical trajectories of motor and cognitive function longitudinally.MethodsCSF neurofilament light protein levels were assessed in 371 PDsporadic, 126 genetic PD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 15 publications
9
32
1
Order By: Relevance
“…In the MSA cohort, pNfL levels slightly positively correlated with the presence of orthostatic hypotension, whereas no significant associations were found in the PSP/CBS and DLB groups. Thus, our results confirm that both cNfL and pNfL concentrations might represent markers of disease severity in PD/PDD, reflecting the intensity of the neurodegenerative process, which could be of importance in future clinical trials 18 21 . The lack of a significant association between NfL values and motor impairment in the MSA and PSP/CBS groups likely depends on the more severe and rapidly progressing neurodegeneration seen in these diseases compared to that in PD 22 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the MSA cohort, pNfL levels slightly positively correlated with the presence of orthostatic hypotension, whereas no significant associations were found in the PSP/CBS and DLB groups. Thus, our results confirm that both cNfL and pNfL concentrations might represent markers of disease severity in PD/PDD, reflecting the intensity of the neurodegenerative process, which could be of importance in future clinical trials 18 21 . The lack of a significant association between NfL values and motor impairment in the MSA and PSP/CBS groups likely depends on the more severe and rapidly progressing neurodegeneration seen in these diseases compared to that in PD 22 .…”
Section: Discussionsupporting
confidence: 79%
“…Spearman’s correlation (rho), univariate and multivariate linear regression models adjusted for age were used to evaluate the association of clinical variables with pNfL and cNFL values, stratified for the diagnostic groups. The results are presented as Beta coefficients (β) and 95% CI 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Certain questions remain regarding the adoption of NfL as a biomarker of diagnosis in PD [ 27 ], such as: what is the probable explanation for documented elevated CSF NfL value only in patients with PD spanning more than 2 years? [ 28 ]. Furthermore, another study found that the temporal dynamics of serum NfL levels in individuals were associated with the conversion from prodromal to PD, suggesting that NfL may not be an early, PD-specific diagnostic biomarker [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic screening for mutations in GBA, LRRK2, parkin , PINK1 and DJ1 was done as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%